PENDIDIKAN DEMOKRASI MELALUI KEGIATAN KULIAH INDUSTRI DI STMIK STIKOM BALI - Ni Nyoman Wulan Antari (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2017)
The College is one objectives of the process formation democratic education through teaching and learning. Unfortunately, this modern era of democratic education was still not thoroughly touched walks of life especially in college. This research was carried out to find out how to exist in one of the democracy education College in STMIK STIKOM Bali. Data collection techniques in the form of interviews, observation, documentation with using qualitative research. Informant research in this research are student Semester II and Management Committee STIKOM Bali. The results of this research are STIKOM Bali democracy education to students through college industry. The lecture is an embodiment of industrial links and match among colleges with the industrialized world. Implementation of the lecture industry conducted two one year periods by presenting the seminar was the entrepreneur IT, stand Expo food by students , education and exhibition of collage. The purpose of the lecture industry activity was held to provide an opportunity to students choosing business freedom what will the group by presenting the entrepreneurial of IT. Application of the democracy education is intended for students as a provision in the industrialized world after their graduation in college.